Ugotavljanje merskih značilnosti lestvic za ocenjevanje atletskega znanja otrok - Železnik Mežan, Lea (Šport (Ljubljana), 2022)
In late childhood, it is very important to acquire new Fundamental movement skills and combine them into complex sport-specific movement skills. A child learns to run, jump and throw during the Fundamental movement phase, but later tries to apply these basic skills to four complexes of basic athletic disciplines. In defining athletic knowledge, it is crucial that the motor tests selected represent all complexes. The aim of our research was to update and adapt the integral model of athletic assessment for children and youths. We wanted to investigate the properties of the new models for assessing six different technical elements of athletics. Forty-five young athletes were included in the study. Their knowledge was recorded with a camera and analysed with rating scales created for this study. There was sufficient variability in the ratings as well as between-subject reliability. We also found that the selected movement tests indicated the same concept – athletic knowledge. The validated instrument could be used in future studies, but has great practical value for coaches and physical education teachers.
Keywords: atleti; atletika; gibalne sposobnosti; gibalno vzgoja; mladostniki; ocenjevanje; otroci; šport